Influence of Furil Dioxime on Cobalt Electrochemical Nucleation and Growth. Issue 2 (23rd January 2020) - Hu, Y.; Lyons, T.; Huang, Q.
Abstract : The nucleation and growth of cobalt (Co) on blanket Si with extremely thin Co seed was studied in the presence of furil dioxime (FD). Cyclic voltammetry (CV), chronoamperometry, and galvanostatic nucleation studies were conducted to understand the effects of FD on Co nucleation process. A potential dependent suppression effect was observed at low potential with a breakdown of the suppression at high potential, resulting in a hysteresis in CV. The potentiostatic current transient experiments showed that side reactions and adsorption process both greatly affected Co nucleation. A well-established model, which deconvolutes the individual contributions to the total current transient, was applied to fit the experimental curves. Progressive and instantaneous Co nucleation were observed across different FD concentrations and applied potentials. Galvanostatic studies further proved the suppression effect of FD and the effects on film morphology were studied at different conditions.